Main Issues of Statistical Analysis in Medical Research - Voxidov Alikul Melitoshevich; Voxidov Dilshod Alikulovich (Genius Journals, 2022)
This work is devoted to the main issues of statistical analysis of clinical trials. Statistical processing is a complex multi-stage process, the level of scientific organization of which decisively determines the quality of the accumulated statistical data, the results of their processing and comprehension.
Keywords: statistical; clinical trials; accumulated